1998
DOI: 10.1177/104063879801000204
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of a Porcine Reproductive and Respiratory Syndrome Virus Vaccine Strain from North American Field Strains by Restriction Fragment Length Polymorphism Analysis of ORF 5

Abstract: Restriction fragment length polymorphism (RFLP) analysis of open reading frame 5 was developed for typing of Czech strains of porcine reproductive and respiratory syndrome virus (PRRSV). e set of restriction enzymes Acc I, Hae II and SnaB I allowed the differentiation of heterogeneous Czech strains of PRRSV clustered separately in the phylogenetic tree. e high-passage strain V-502 (164) was also differentiated from its parent strain V-502. e same restriction enzymes could distinguish the European-type vacci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
105
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(108 citation statements)
references
References 13 publications
(16 reference statements)
3
105
0
Order By: Relevance
“…4,5 This study identified all of these except type 1-8-2. As well, 17 additional RFLP types of the virus were identified in this study.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…4,5 This study identified all of these except type 1-8-2. As well, 17 additional RFLP types of the virus were identified in this study.…”
mentioning
confidence: 99%
“…2 In addition to detection of the virus, RT-PCR RFLP typing methods have been developed that make it possible to differentiate different field strains and the commercial vaccine. 4 The current study detected and typed PRRSV using PCR-based methods from clinical samples ob-tained from Ontario swine herds from January 1998 to July 2000.…”
mentioning
confidence: 99%
See 3 more Smart Citations